2014
DOI: 10.1187/cbe-13-04-0085
|View full text |Cite
|
Sign up to set email alerts
|

Putting PhDs to Work: Career Planning for Today's Scientist

Abstract: The authors examined individual development plan (IDP) awareness and use, the benefits of creating an IDP, and ways to facilitate IDP use by administering surveys to postdoctoral researchers, mentors, and administrators.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
45
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(56 citation statements)
references
References 14 publications
7
45
2
Order By: Relevance
“…Advisor Buy-In Some of our experiences and feedback point to the importance of advisor buy-in and engagement, consistent with other studies that find advisees are more likely to value the IDP process if their advisor also does (e.g., Hobin et al, 2014). In other words, this process is not a fix for a disengaged advisor or one who is dismissive of non-academic careers.…”
Section: Expanded Mentoring Networksupporting
confidence: 87%
See 1 more Smart Citation
“…Advisor Buy-In Some of our experiences and feedback point to the importance of advisor buy-in and engagement, consistent with other studies that find advisees are more likely to value the IDP process if their advisor also does (e.g., Hobin et al, 2014). In other words, this process is not a fix for a disengaged advisor or one who is dismissive of non-academic careers.…”
Section: Expanded Mentoring Networksupporting
confidence: 87%
“…While data on IDP effectiveness are sparse and generally based on small sample sets, initial studies are promising (e.g., Tsai et al, 2018). A 2014 survey of postdocs (Hobin at al., 2014) found relatively low usage rates but high perceived value among those who had used IDPs (71% of postdocs, 90% of mentors).…”
mentioning
confidence: 99%
“…Compared to the 2014 study in which 19% of postdoctoral researchers used the IDP and 71% of users found it valuable 4 , the current data suggests that there has been a general increase in IDP usage among postdoctoral researchers with 54.1% of respondents in this study indicating that they are required to complete an IDP while its perceived value has decreased to less than 40%.…”
Section: Discussioncontrasting
confidence: 80%
“…The Individual Development Plan was first introduced by the U.S. Federation of American Societies for Experimental Biology in 2002, and in 2014 the National Institutes of Health implemented a policy requiring the reporting of the tool's use by graduate students and postdoctoral researchers in grant progress reports [1][2][3] . Also in 2014, 19% of postdoctoral researchers were shown to use the IDP with 71% of those users finding it valuable 4 . We recently conducted a multi-institutional study on the use and effectiveness of the IDP in 663 PhD students and found that 57% completed an IDP and 51% of users reported it being useful to their career development 5 .…”
Section: Introductionmentioning
confidence: 99%
“…With the added pressure of graduating in a timely fashion for PhD trainees and obtaining a tenure-track faculty position for postdoctoral scholars, little time is protected for trainees to focus on developing other necessary skills for successful careers [1, 12–15]. This suggests that colleges and universities should be striving to provide additional resources and support to graduate students and recent PhD graduates as they strive to obtain careers within nonacademic settings [13, 5, 9, 1719]. More attention should be concentrated on educating trainees on career options and how to strengthen their transferable skills through engaging and relevant experiences.…”
Section: Introductionmentioning
confidence: 99%